2014
DOI: 10.1371/journal.pone.0112660
|View full text |Cite
|
Sign up to set email alerts
|

Functional Heterologous Protein Expression by Genetically Engineered Probiotic Yeast Saccharomyces boulardii

Abstract: Recent studies have suggested the potential of probiotic organisms to be adapted for the synthesis and delivery of oral therapeutics. The probiotic yeast Saccharomyces boulardii would be especially well suited for this purpose due to its ability, in contrast to probiotic prokaryotes, to perform eukaryotic post translational modifications. This probiotic yeast thus has the potential to express a broad array of therapeutic proteins. Currently, however, use of wild type (WT) S. boulardii relies on antibiotic resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…During this assay, a pRS42K plasmid carrying the S. cerevisiae TDH3 promoter was used, indicating that the S. cerevisiae TDH3 promoter is working in S. boulardii. A previous study indicated that heterologous GFP can be expressed in S. boulardii (15). Here, mito-GFP and mito-RFP were functionally expressed and precisely localized to mitochondria, as expected, which means that even the localization of heterologous protein can be precisely achieved in S. boulardii.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…During this assay, a pRS42K plasmid carrying the S. cerevisiae TDH3 promoter was used, indicating that the S. cerevisiae TDH3 promoter is working in S. boulardii. A previous study indicated that heterologous GFP can be expressed in S. boulardii (15). Here, mito-GFP and mito-RFP were functionally expressed and precisely localized to mitochondria, as expected, which means that even the localization of heterologous protein can be precisely achieved in S. boulardii.…”
Section: Discussionsupporting
confidence: 82%
“…Second, the efficiencies of genetic perturbations are as high as 100%, and target genetic perturbations are made due to the precise cutting and almost no off-target effects of the CRISPR-Cas9 system in yeast. This is a key advantage compared to UV mutagenesis (14,15), as the latter generates numerous unwanted mutations throughout the whole genome. Off-target mutation effects caused by CRISPR-Cas9 in mammalian systems have been reported previously (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some transformation strategies require auxotrophic mutant strains, which lack the ability to synthesize an organic molecule, e.g., an amino acid, which can be restored upon transformation with a bicistronic plasmid encoding both a protein which will produce per turn that organic molecule and a desired foreign sequence to be expressed. So far, no natural auxotrophic mutants of S. boulardii have been reported and only recently auxotrophic strains of this probiotic yeast were obtained by UV mutagenesis (Hamedi et al 2013;Hudson et al 2014). Hamedi and colleagues elegantly described the first URA3 S. boulardii mutants (Hamedi et al 2013), obtained by mutagenesis of the wild-type strain lyo derived from DiarSafe, produced by the British company Wren Laboratories, Ltd.…”
Section: Genetic Engineering and Heterologous Protein Expression In Smentioning
confidence: 99%
“…Numerous studies have investigated the use of probiotic bacteria for the delivery of gastrointestinal therapeutics; however, eukaryotic probiotics have been less well studied. A major advantage of using probiotic yeast for this application is their ability as eukaryotes to create post-translational modifications that might enable expression of a wide variety of therapeutic proteins in their proper conformation [10]. Live Saccharomyces cerevisiae cells are employed as biotherapeutic or probiotic agents for re-equilibration of intestinal microflora, and the latest studies have demonstrated their efficacy in treating chronic or recurrent diarrhea, especially in those cases associated with clostridium difficile [11].…”
Section: Introductionmentioning
confidence: 99%